The Implementation Of Citizen Complaint System In Cipete Selatan Rw 003 Based On Website Using Agile Method: Enhancing Community Engagement and Service Efficiency - Anang Akbar Yulianto (PT Triputra Sejahtera Prima, 2024)
This research aims to enhance the process of collecting and handling complaints in the community of Cipete Selatan RW 003 through the implementation of a website-based complaint system using the Agile method. Utilizing information technology, this system allows citizens to easily submit complaints and monitor the status of their complaints online. The Agile method is employed to ensure that the system development is flexible and responsive to changes in user needs. Implementation steps include requirement gathering, system design, development, testing, and deployment. Evaluation is conducted on the implemented system to assess performance, effectiveness, and user satisfaction. The research findings indicate that the implementation of a website-based complaint system using the Agile method can improve the optimization of the complaint collection and handling process, increase transparency, and encourage active citizen participation in enhancing the overall quality of the complaint system. This research contributes to the development of a complaint system that is responsive to community needs and can serve as a guide for implementing similar systems in other community environments.